2013
DOI: 10.4187/respcare.02816
|View full text |Cite
|
Sign up to set email alerts
|

Influence of FIO2on PaCO2During Noninvasive Ventilation in Patients With COPD

Abstract: BACKGROUND:The administration of a high F IO 2 to COPD patients breathing spontaneously may result in hypercapnia, due to reversal of preexisting regional hypoxic pulmonary vasoconstriction, resulting in a greater dead space. Arterial blood gas trends have not been reported in these patients. In a 31-bed medical ICU in a teaching hospital we prospectively investigated the response of 17 CO 2 -retaining COPD patients, after acute respiratory crisis stabilization with noninvasive ventilation, to an F IO 2 of 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…PaCO 2 and PaO 2 are not necessarily proportional. Once hyperventilation sets in, blood gas exchange in the patient’s alveoli is restricted; PaO 2 may also decrease significantly [ 30 ]. The results of our meta-analysis have found that compared with NIV, HFNC is more beneficial in reducing the PaCO 2 level, length of hospital stay and the incidence of nasal facial skin breakdown, no effect differences in the PaO 2 , the incidence of tracheal intubation and mortality were found between HFNC and NIV treatments.…”
Section: Discussionmentioning
confidence: 99%
“…PaCO 2 and PaO 2 are not necessarily proportional. Once hyperventilation sets in, blood gas exchange in the patient’s alveoli is restricted; PaO 2 may also decrease significantly [ 30 ]. The results of our meta-analysis have found that compared with NIV, HFNC is more beneficial in reducing the PaCO 2 level, length of hospital stay and the incidence of nasal facial skin breakdown, no effect differences in the PaO 2 , the incidence of tracheal intubation and mortality were found between HFNC and NIV treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the present approach is that all COPD cases were confirmed using spirometry ( Fig. 1 ), whereas in the majority of previous studies 5 , 6 , 19 , 21 , 26 , 27 , 28 this approach was not used for the COPD diagnosis. 1 Furthermore, other clinical conditions than COPD that could be responsible for acute respiratory failure and represented potential confounding elements in previous works were not included.…”
Section: Discussionmentioning
confidence: 85%
“…In conclusion, our study had the clear objective of evaluating the safety of brief increases in F IO 2 (during respiratory therapy procedures and during O 2 saturation decreases secondary to maladjustments or interface leaks) in CO 2 -retaining subjects with COPD and undergoing NIV. 10 No other clinical objective exists in sustained increases in F IO 2 , except temporarily, because in cases of persistent refractory hypoxemia, endotracheal intubation and mechanical ventilation are mandatory.…”
Section: Influence Of F Io 2 On P Aco 2 In Copd Patients With Chronicmentioning
confidence: 99%